PENINGKATAN DAYA SAING MELALUI STRATEGI PEMASARAN JAMUR TIRAM PUTIH (STUDI KASUS) DI DESA BEKUT - Cerah, Susilawati; Syahnaz, Erifa (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
One of the food sources that contains high vegetable protein is oyster mushroom. An oyster mushroom cultivation business in Bekut Village, Tebas district, Sambas was run by Mr. Agustipar since 2016. However, the fresh packaging of oyster mushroom only can be stored in short period of time. Therefore, the appropriate packaging strategy plays an important role in succeeding the marketing of oyster mushroom. The marketing strategy of oyster mushroom is influenced by internal factors (strengths and weaknesses) and external factors (opportunities and strengths). As a result, it is necessary to conduct a study on the oyster mushroom marketing strategy run by Mr. Agustipar. SWOT analysis was performed to analyze the data. It was found the internal factors such as having: sufficient capital, skilled labors, non-chemical food products, good quality products, a stable, affordable selling price, permanent consumers, the production of oyster mushroom has not met the demand, short-period time of product storage, and no intense promotion. The external factors are: the marketing opportunity is high, increasing demand of the product, consumers’ loyalty, expanding marketing network, the existence of the similar business, increasing price of the raw material. Based on the result of SWOT analysis, there were oyster mushroom marketing strategies found. They are: maintaining the quality of oyster product and stable selling price, production and sales forecasting, print media, electronic media, and social media promotion, increasing product efficiency for competition, and establishing the cooperation with companies or UMKM processing oyster mushroom.Keywords: Marketing strategy, Oyster mushroom, SWOT analysis